THE DEVELOPMENT OF COMICS FOR LEARNING TO ENHANCE THE CAPACITY OF STUDENTSâ EMPATHY ON THIRD GRADER STUDENTS AT PRIVATE PRIMARY SCHOOL OF 17 AGUSTUS TEBET SOUTH JAKARTA - Karlina Marjo, Happy (Jurnal Konselor, 2015)
The purpose of this research is to develop a medium learning of comic learning titledâAyok! Belajar Berempati Bersama Teman-temanâ which was assumed to be useful to engage empathy of third graders at SDS 17 Agustus Tebet South Jakarta. The method used in this research was research and development with technique of analyzing the quantitative data and descriptive statistic technique though developmental model which was orientated toward the result of developmental model of Baker and Schutz with the procedures of the research a follows:( 1 ) analyzing the needs, ( 2 ) specifying the learning,( 3 ) composing the blue-print of instruments, ( 4 ) producing comic development, ( 5 ) trialing the products, ( 6 ) revising the products, ( 7 ) Analyzing all the processes of development from the beginning until the end. The research produced a comic learning empathy entitled âAyok! Belajar Berempati Bersama Teman-temanâ divided into two parts for the kids and the tutors, which the appropriateness was very high based on the results of a review from the experts as 83,8 % . The results of the trial showed that the comics gave improvement upon studentsâ empathy as 25,74 % .Keyword: comic learning, empathy